2013
DOI: 10.1080/17470218.2012.704052
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics matters: A new eye-tracking investigation of animated triangles

Abstract: Eye movements have been recently recorded in participants watching animated triangles in short movies that normally evoke mentalizing (Frith-Happé animations). Authors have found systematic differences in oculomotor behaviour according to the degree of mental state attribution to these triangles: Participants made longer fixations and looked longer at intentional triangles than at triangles moving randomly. However, no study has yet explored kinematic characteristics of Frith-Happé animations and their influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 53 publications
(73 reference statements)
4
17
0
Order By: Relevance
“…The eyetracking results revealed that individuals with and without schizophrenia showed a similar modulation of eye movements in response to the different conditions of the Frith-Happé animations. First, both groups showed the same increase in fixation duration from R to ToM animations, consistently with previous studies 42 46 47 48 . This suggests an equal increase in cognitive processing related to the integration of mental states in patients as in controls.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The eyetracking results revealed that individuals with and without schizophrenia showed a similar modulation of eye movements in response to the different conditions of the Frith-Happé animations. First, both groups showed the same increase in fixation duration from R to ToM animations, consistently with previous studies 42 46 47 48 . This suggests an equal increase in cognitive processing related to the integration of mental states in patients as in controls.…”
Section: Discussionsupporting
confidence: 90%
“…Secondly, gaze directed to the triangles were longer from R to GD to ToM, thus suggesting that eye movements were preferentially drawn to social agents 46 . Finally, it has been suggested that eye tracking differences between ToM and GD were explained by idiosyncratic low-level kinematic properties of the Frith–Happé animations, whereas the differences between R on the one hand and GD/ToM, on the other hand, remained significant even after taking into account kinematic confounds 47 . Thus, the eye tracking measures gathered on Frith-Happé animations can be considered as quantitative and implicit markers of intentional interpretations 48 .…”
mentioning
confidence: 99%
“…While the pursuit identification procedure used in the current study is laborious and complicated, we currently don’t see any better alternative. One popular strategy is to digest raw eye movements with an algorithm that extracts only fixations and saccades (e.g., Klein et al, 2009 ; Roux, Passerieux & Ramus, 2013 ). Episodes of smooth eye movement are then decomposed into fixations.…”
Section: Discussionmentioning
confidence: 99%
“…Their judgments may thus reflect the task demands rather than attributes of human perception. With regard to the stimuli, Roux, Passerieux & Ramus (2013) showed that a difference in the total fixation time dedicated to a pair of moving objects in two different hand-tailored displays used in Klein et al (2009) disappears once the distance between the two objects is controlled. Finally, researchers offered computational level analyses ( Feldman & Tremoulet, 2008 ; Baker, Saxe & Tenenbaum, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the heat-seeking direction explicitly modeled here, other motion cues may also impact the performance of search-for-chase, such as spatial proximity (e.g., Roux, Passerieux, & Ramus, 2013;Meyerhoff, Schwan & Huff, 2014b). Recent studies have shown that reduced inter-object spacing guides visual attention and eye movements in dynamic multi-objects displays (Galazka & Nystr€ om, 2016;Meyerhoff, Schwan & Huff, 2018;Zelinsky & Todor, 2010).…”
Section: A Linear Effect Of Set-size and Beyondmentioning
confidence: 99%